BioMar-ACG: A successful partnership to inventory and promulgate marine biodiversity - Cortés Núñez, Jorge (2020)
Initiated in 2015, the marine inventory of Área de Conservación Guanacaste (BioMar-ACG) is rapidly advancing knowledge of biodiversity. Key aspects include synergizing with parataxonomists, barcoding specimens and making information available. After 85 years, 594 species were reported. Now, after four years, BioMar-ACG documented 1,123 species, for a total of 1,479.